The dynamics of the focal qualities in girls aged 10-15 years - S.B. Samonenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : determine the dynamics of focal qualities in girls of secondary school age. Material : is used stabiloanalizer with biofeedback STABILAN-01. The study involved 254 girls (age - 10-15 years). To assess the temporal and spatial parameters of motor actions reproduce the trajectory of the girls (which is shaped like a triangle) and the rate of passage. Results : the obtained data on averages percent error when playing a temporal and spatial parameters of motor actions girls. Revealed that girls have a better ability to manage spatial than temporal parameters of motor coordination. A high coefficients of variation in all parameters. Conclusions : the results indicate large individual differences in the level of development of coordination abilities of girls at this age. This is reflected in the effectiveness of teaching motor actions. Also confirms the assumption about the possibility of taking into account these indicators as criteria for selecting a method of differentiated teaching motor actions of girls of secondary school age.